Pemodelan Unconventional Intersection Berbentuk Partial Cloverleaf (Parclo B2) dengan Microsimulation Program PTV. VISSIM. 9 - Bagas Haryo Wicaksono; Muchlisin Muchlisin (Bulletin of Civil Engineering, 2022)
Before 2020, Kentungan is the one of the densest intersections in Yogyakarta. This intersection is important due to it connected with all primary roads across level of the authority. Therefore, this intersection will be modified in the form of an unpassed intersection (underpass). The purpose of this study is to explore the model of the unconventional form of the intersection with the form of Partial Cloverleaf B2 (Parclo B2), thus that it can be optimized in traffic performance and safety. The method used in this study is the use of a software microsimulation program, PTV. Vissim 9, which models 3 scenarios, namely existing conditions, the Parclo B2 model with the default form, and the Parclo B2 model with modifications. Based on the three results of the model, the existing conditions that initially had a Level of Service (LOS) F with a delay value of 104.79 seconds can rise with LOS D with a value of 54.9 seconds. Based on the models result, Partial Cloverleaf B2 (Parclo B2) is able to reduce traffic congestion even though it still has some advantages and disadvantages.